2021
DOI: 10.3389/fonc.2021.777037
|View full text |Cite
|
Sign up to set email alerts
|

The ncRNA-Mediated Overexpression of Ferroptosis-Related Gene EMC2 Correlates With Poor Prognosis and Tumor Immune Infiltration in Breast Cancer

Abstract: Ferroptosis is an iron-dependent programmed cell death process. Although ferroptosis inducers hold promising potential in the treatment of breast cancer, the specific role and mechanism of the ferroptosis-related gene EMC2 in breast cancer have not been entirely determined. The potential roles of EMC2 in different tumors were explored based on The Cancer Genome Atlas (TCGA), Genotype-Tissue Expression (GTEx), Gene Expression Profiling Interactive Analysis 2 (GEPIA2), Tumor Immune Estimation Resource (TIMER), S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…We found that proteins associated with longer PFS were most highly correlated with ES-TIL tumors, followed by S-TIL, and less so in those classified as N-TIL. We identified fifteen proteins that strongly correlated with PFS in our cohort, independent of common covariates of disease progression (e.g., patient age at diagnosis, disease stage and residual disease status), that included several proteins known to regulate antigen presentation 36 (TAP2, adjusted hazard ratio, aHR = 0.76, p = 0.02), T-cell activation 37 (SPN, aHR = 0.7, p = 0.014) and have further been correlated with regulating immune cell infiltration in other organ-site malignancies 38 (EMC2, aHR = 0.27, p = 4.4E−4). We investigated these immune-related candidates in transcript data from an independent cohort of 126 HGSOC patients 15 , many of whom survived greater than 10 years, and confirmed that these 15 immune-related proteins strongly correlate with PFS and OS.…”
Section: Discussionmentioning
confidence: 99%
“…We found that proteins associated with longer PFS were most highly correlated with ES-TIL tumors, followed by S-TIL, and less so in those classified as N-TIL. We identified fifteen proteins that strongly correlated with PFS in our cohort, independent of common covariates of disease progression (e.g., patient age at diagnosis, disease stage and residual disease status), that included several proteins known to regulate antigen presentation 36 (TAP2, adjusted hazard ratio, aHR = 0.76, p = 0.02), T-cell activation 37 (SPN, aHR = 0.7, p = 0.014) and have further been correlated with regulating immune cell infiltration in other organ-site malignancies 38 (EMC2, aHR = 0.27, p = 4.4E−4). We investigated these immune-related candidates in transcript data from an independent cohort of 126 HGSOC patients 15 , many of whom survived greater than 10 years, and confirmed that these 15 immune-related proteins strongly correlate with PFS and OS.…”
Section: Discussionmentioning
confidence: 99%
“…starBase (ENCORI: The Encyclopedia of RNA Interactomes. (sysu.edu.cn)) is a database for exploring miRNA-related studies [30,31]. We use starBase to perform the expression correlation analysis for miRNA-LPCAT1, lncRNA-has-miR-218-5p and lncRNA-LPCAT1 in BRCA.…”
Section: Starbase Database Analysismentioning
confidence: 99%
“…Cancer treatment has rapidly evolved into immunotherapy, and the effective therapy of established tumors necessitates rational multi-combination immunotherapy including ferroptosis. Recently, many studies have reported the interaction between ferroptosis modifications and antitumor immunity [4][5][6][7][8][9][10][11][12] . Ferroptosis, characterized by iron-dependent accumulation of lipid peroxides 13 ,…”
mentioning
confidence: 99%